Geographical Proximity, the Dynamics of Competitiveness Clusters and Industrial Policy: Some Lessons from a French Case Study - Patrick Dieuaide; Yohan Rochefeuille (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2018)
The article examines the evolution of cooperative relations within a French competitive cluster located in the Paris region, the ‘Systématic’ cluster. He questions the importance of geographical proximity as a basis for setting up and developing knowledge transfers. From an exhaustive list of labeled RandD projects within the cluster, between 2005 and 2015, the article verifies this hypothesis and confirms Krugman's analyzes and Feldman on the importance of externalities to understand the phenomenon of collocated activities. But the article also highlights the importance of non-spatial proximities (organizational, institutional and social) to understand the dispersion of companies outside the cluster and draws some lessons for the industrial policy of competitiveness clusters.